BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN KINERJA PEGAWAI - Mulyati, Rini (Jurnal Ilmu Administrasi Negara, 2016)
Organizational Culture, Leadership Style and Performance Officer. This study aims to identify and analyze the influence of organizational culture and leadership style on employee performance BPMP2T Pelalawan. This type of research is a survey research with a quantitative approach. The study population 34 employees and all sampled. Data collection techniques used in this study using questionnaires and documentation regarding the issues examined. Analysis of data using multiple linear regression. The results showed, the value of organizational culture variable t is greater than t α / 2, ie 2.730> 2.021 with a significance level of 0,010 t, then the partial organizational culture has a positive influence on employee performance, with 95% confidence. Value leadership style variable t is greater than t a / 2, ie 2.724> 2.021 with a significance level of 0,010 t, then the partial leadership style has a positive and significant impact on employee performance, with a confidence level of 95%. The coefficient of determination (R2) of the model is 0463, which means that 46.3% of the independent variables (organizational culture and leadership style) is able to explain the dependent variable (performance of employees) and the remaining 53.7% is influenced by other variables outside variables in the study this.